Evaluating the feasibility and effectiveness of a mindfulness-based intervention on stress and anxiety of family caregivers managing peritoneal dialysis - Fazila Aloweni; Kinjal Doshi; Nurliyana Agus; Stephanie Fook-Chong; Sin Yan Wu; Lau Peng Kong; Marjorie Foo; Elena M Ayob; Truls Ostbye (Proceedings of Singapore Healthcare, 2022)
Background Mindfulness-based intervention (MBI) has not been evaluated for its feasibility and effectiveness in reducing stress and anxiety among family caregivers of patients on peritoneal dialysis (PD). Objectives (1) To evaluate the feasibility to include MBI during PD training for family caregivers. (2) To determine the effect of MBI on the caregivers’ levels of stress (perceived stress scale, PSS), anxiety state-trait anxiety inventory, STAI), QOL (short-form 36) and reactions to caregiving (caregiver reaction assessment, CRA). (3) To determine differences in the health-related QOL (Kidney Disease Quality of Life Instrument-Short Form , KDQOL PCS and SF-36 MCS) of care recipients with caregivers receiving MBI at 1 month, 3 months and 6 months when compared to those with caregivers receiving routine training. (4) To gather the caregiver’s feedback on the MBI. Methods This feasibility study recruited family caregivers to receive either mindfulness training (MT) or treatment-as-usual (TAU) group. Both groups received 4.5-days of structured PD training, but only caregivers in the MT group received 4 days of MT sessions, audio-guided mindfulness practice at home and weekly telephone follow-up. Results Forty-four family caregivers participated in this study. Including MBI as part of the PD training was feasible. There was a trend towards lower scores for PSS and T-STAI in the MT group compared to the TAU group. The baseline score of both PSS and T-STAI were positively correlated with post-intervention outcome scores. Conclusions Mindfulness-based intervention has the potential to improve psychological symptoms among caregivers of patients with PD.